Helman defends decision to pull VA sponsorship of Veterans day parade - Robbins RA (Southwest Journal of Pulmonary and Critical Care, 2013)
No abstract available. Article truncated after 150 words. Sharon Helman, Phoenix VA Director, defended her decision to cancel VA sponsorship of the annual Phoenix Veterans Day Parade in a 4/10/13 email to VA employees. Helman said that VA sponsorship was cancelled because of “…priorities in the organization (specifically access), and heightened awareness over liability concerns which VA Legal Counsel brought forward”. She concluded her letter by warning “… that all media inquiries should be forwarded to Paul Coupaud, Acting Public Affairs Officer”. VA officials initially said fear of litigation prompted the review of VA support. Last year, a float carrying wounded Veterans in a Midland, Texas, parade collided with a freight train, killing four and injuring 17. Crash victims and their families filed lawsuits in Texas against Union Pacific Railroad and the float owner. The VA was not a defendant, and the VA has not issued any national directives on liability as a result of the tragedy.In…